Predicción de la relación diámetro – altura comercial en las plantas de Tapirira guianensis Aubl. según tipo de muestra en bosque natural, Puerto Almendra, Loreto, Perú – 2023 - Chota Mendoza, Christma (2024)
The aim of this study was to determine the relationship between diameter and merchantable height in Tapirira guianensis Aubl. “huira caspi” plants in different sample types within a natural forest. Ninety-two trees with DBH ≥ 10 cm were used; four samples were evaluated: the first had two diameter classes, the second four, the third six, and the fourth sample comprised 36 individuals. The cubic allometric model showed the best fit to the diameter - mercenary height relationship in Tapirira guianensis Aubl. “huira caspi” plants, with a good degree of correlation. The chosen prediction equation was ŷ = -9.239 + (1.941 x t) + (-0.049 x t²) + (0.000 x t³).